The hill [videorecording (DVD)] - Pizzo, Angelo; Smith, Scott Marshall; Quaid, Dennis; Ford, Colin, 1996-; Carter, Joelle; Houser, Randy; Devoti, James; Berry, Jesse; Bedelia, Bonnie, 1946-; Glenn, Scott, 1942-; Kimlin, Kristopher S.; Zanelli, Geoff, 1974- (Universal, 2023)
The inspiring true story of Rickey Hill, the small-town son of a traveling Pastor. A sandlot baseball phenom, Rickey defiantly overcomes his physical disabilities and father's persistent worry for his health, to fulfill his dream of playing professional baseball and ultimately transforming his connection with his father.